Freqüência de suplementação e fonte de nitrogênio suplementar e sua relação com o valor alimentar de dietas baseadas em feno de quicuio (Pennisetum clandestinum) fornecidas para ovinos - Cadorin Junior, Rui Luiz (2008)
An in vivo digestibility experiment was conducted to evaluate the influence of degradable nitrogen source and feeding frequency on the digestion process and utilization of kikuio grass hay. Eight castrated male lamb (35 ± 4 Kg live weight) maintained in individual metabolic cage, were used in a 2x2 factorial experiment according to a replicated 4x4 Latin Square design. Treatments tested were the combination of two supplement feeding frequencies: once (morning) or twice (morning and aftermoon) daily, and two supplements, based on cassava meal plus calcium caseinate or cassava meal plus urea. For all treatments kikuio hay was fed ad. Libitum and the supplements were fed at a rate of 7 g/Kg live weight daily. Animals supplemented twice day consumed higher quantity of the gross fractions, either in absolute values or in proportion to live weight or metabolic weight (P<0,05) and they tended to consume higher quantity of digestible energy and to synthesize more microbial protein (P<0,10). Feeding frequency did not influence the digestibility. When calcium caseinate was fed animal tended (P<0,10) to have higher dry matter intake in relation to live weight and higher organic matter intake in relation to metabolic weight. There was interaction between nitrogen source × frequency of supplementation on intake of both digestible organic matter and digestible energy. Animals receiving supplement with calcium caseinate twice a day and supplemented with urea once a day have higher intake of theses fractions. Animals supplemented once a day presented higher rumen sugar concentration (P<0,05), but pH as well as ammonia and peptides + aminoacid concentration were not affected by supplementation frequencys. Higher concentrations of NH3 and lower concentrations of pep+aa were observed in animals supplemented with urea (P<0,05). The supplement feeding frequency did not influence the digestion process and forage utilization when the nitrogen source was urea, but when the nitrogen source was calcium caseinate, supplementation twice daily improves intake and nutrients offer to the animals.